2004
DOI: 10.1042/bj20040792
|View full text |Cite
|
Sign up to set email alerts
|

The strong efficiency of the Escherichia coli gapA P1 promoter depends on a complex combination of functional determinants

Abstract: The Escherichia coli multi-promoter region of the gapA gene ensures a high level of GAPDH (glyceraldehyde-3-phosphate dehydrogenase) production under various growth conditions. In the exponential phase of growth, gapA mRNAs are mainly initiated at the highly efficient gapA P1 promoter. In the present study, by using site-directed mutagenesis and chemical probing of the RPo (open complex) formed by Esigma70 (holoenzyme associated with sigma70) RNAP (RNA polymerase) at promoter gapA P1, we show that this promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 47 publications
2
38
0
Order By: Relevance
“…Our finding that a 218T/G substitution in cesTp reduced promoter activity fourfold compared with wild-type cesTp (Fig. 3) is in agreement with studies with the gapA1 promoter which showed that a 218T/G substitution reduced promoter activity threefold (Thouvenot et al, 2004). It has been demonstrated that there is a preference for T at position 218 in E. coli promoters (Singh et al, 2011) and that this position may contribute to a structural conformation favourable for Es 70 interactions (Murakami et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Our finding that a 218T/G substitution in cesTp reduced promoter activity fourfold compared with wild-type cesTp (Fig. 3) is in agreement with studies with the gapA1 promoter which showed that a 218T/G substitution reduced promoter activity threefold (Thouvenot et al, 2004). It has been demonstrated that there is a preference for T at position 218 in E. coli promoters (Singh et al, 2011) and that this position may contribute to a structural conformation favourable for Es 70 interactions (Murakami et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, it was observed earlier (32) that promoters containing Ϫ15 TG Ϫ14 are able to tolerate weaker Ϫ10 elements. Furthermore, both gapAP1 and Pminor promoters have weak Ϫ10 elements, and the presence of a strong Ϫ15 element is required for promoter function (21,49). On the other hand, mutations that improve the Ϫ10 element were shown to abolish the requirement for a strong Ϫ15 element, therefore demonstrating the direct role of the Ϫ15 element in complementing weak Ϫ10 element strength.…”
Section: Discussionmentioning
confidence: 99%
“…1C). Our previous work demonstrated that P minor and P min belong to a newly identified promoter class, Ϫ 35/TGn, that is characterized by a requirement for both an excellent Ϫ35 element and an extended Ϫ10 TGn sequence to compensate for a poor Ϫ10 element (1,37,38). To investigate whether the effect of region 1.1 with P minor reflects a general characteristic of Ϫ35/TGn promoters, we compared the formation of active transcription complexes at P min with that at P min16 , a derivative with perfect Ϫ35 and Ϫ10 elements, and at P min7 , a derivative with a good Ϫ35 and a perfect TGn and Ϫ10 element (Fig.…”
Section: Effectmentioning
confidence: 99%
“…Previously, it has been shown that a spacer can influence promoter activity (38,(40)(41)(42)(43)(44)(45). In particular, a GC-rich spacer can result in reduced promoter activity compared with that seen with an AT-rich spacer (39,40).…”
Section: Effectmentioning
confidence: 99%